KARAKTERISKTIK BACKSCATTER CITRA ALOS PALSAR POLARISASI HH DAN HV TERHADAP PARAMETER BIOFISIK HUTAN DI SEBAGIAN TAMAN NASIONAL KERINCI SEBLAT - nirmawana Simarmata (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2017)
Synthetic Aperture Radar (SAR) is one kind of an active remote sensing system, utilizing microwave to records the earth surface. One of the SAR’s satellites is ALOS PALSAR which is capable of penetrating clouds so that the underlying objects can be identified. ALOS PALSAR has a polarization system operating with single beam polarization (HH or HV), dual polarization (HH + HV or VV + VH) and full polarization (HH + HV + VH + VV). This study aims to use the backscatter value of ALOS PALSAR's image for monitoring and mapping the forest. The Utilization of ALOS PALSAR imagery to measure forest biophysical parameters and saturation levels identified based on backscatter sensitivity. Image extraction is done through image calibration where the digital value is converted to sigma naught backscatter value then the result of calibration unit is changed to decibels. Backscatter sensitivity depends on forest structure which can affect scattering mechanism. The backscatter value is also influenced by humidity and weather dynamics which can also affect the dielectric constant. The result of accurate classification of land use polarization fall in HH accuracy of 62,4%. Whereas for HV polarization accuracy obtained equal to 74,88%.